Effect of Substrates' Compliance on the Jumping Mechanism of Locusta migratoria - Mo, Xiaojuan; Romano, Donato; Miraglia, Marco; Ge, Wenjie; Stefanini, Cesare (Frontiers in Bioengineering and Biotechnology, 2020)
Locusts generally live and move in complex environments including different kind of substrates, ranging from compliant leaves to stiff branches. Since the contact force generates deformation of the substrate, a certain amount of energy is dissipated every time a locust jumps from a compliant substrate. In all researches conducted, only tree frogs have proved to be capable of recovering, just before leaving the ground, part of the energy that had been accumulated in the substrate as deformation energy in the initial pushing phase. The jumping performances of adult Locusta migratoria on substrates of three different compliances demonstrate that locusts are able to adapt their jumping mode to the mechanical characteristics of the substrate. Recorded high speed videos illustrate the existence of deformed substrate’s recoil before the end of the take-off phase when locusts jump from compliant substrates, which indicates the ability of recovering part of energy from the substrate deformation. This adaptability is supposed to be related to the catapult mechanism adopted in locusts’ jump thanks to their long hindlegs and sticky tarsus. These findings improve the understanding of the jumping mechanism in locusts, as well as can be used to develop artifact outperforming current jumping robots in unstructured scenarios.